GOD HAS SIGNED: Nature, Divinity and Mysticism in the Poetry of Kuvempu - B, Abhaya N. (Journal of Dharma, 2014)
Kuvempu wrote a large number of poems on the mysteries of nature. Kuvempu hails from the heart of Western Ghats and he spent his childhood and youth exploring the forests around his house. Untrammelled nature was both mysterious and beautiful; hence nature turned out to be a primary inspiration to write poetry. Kuvempu looks outward, seeking to comprehend the oneness of all in nature through his senses. But he is also struck by the inability to comprehend and explain nature through senses. Often he expresses his awe at natural sights such as dawn (which appears to him as a God’s signature) or the greenery of Western Ghats (which seems to have painted everything in nature in green, including poet’s soul and the blood in the stomach). This leads Kuvempu to resort to mysticism in order to relate, comprehend and sing about nature. He sees in nature the divine presence. The paper will analyze poems such as Devaru Rujumadidanu, Ba Phalguna Ravidarshanake, and Prakriti Upasane, and explore the poetic perception of nature as divine through mysticism.